THE INFLUENCE OF CONSUMER PREFERENCES ON CHINESE PRODUCT EXPORTS THROUGH SHOPEE TO THAILAND UNDER COVID-19 - Guan Chaojie; Tubagus Achmad Darodjat (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
Since 2019, COVID-19 has spread worldwide, affecting numerous nations and regions. Many businesses felt the effects of the economy and epidemic policies. The e-commerce sector has increased throughout this time as well. Through cross-border marketplaces like Shopee, which allows many Chinese people to sell their goods to the Thai market, many Chinese vendors will sell their wares. Recognizing consumer preferences changes during the epidemic is crucial for boosting sales. Based on a current literature review, theory, quantitative analysis, research definitions, and design of questionnaires in accordance with the view and related requirements, this paper expands the study of consumer preferences to the field of cross-border logistics. Survey results are collected, data is analyzed using SPSS software, the analysis process is discussed, the findings are summarized, and the study is completed. According to the study, retailers' decision-making on product selection and pricing is mainly influenced by the effects on various consumer types, including the purchasing process, sex, earnings, and existing policies. The research findings in this article recommend that cross-border e-commerce businesses offer differentiated offerings following various target markets, which is essential for cross-border e-commerce to cut costs further and boost export efficiency.